Systemic lupus erythematosus presenting as toxic epidermal necrolysis: a case report - Sandhu, Jaskirat Kaur; Rai, Seema; Sandhu, Kirat Kaur (International Journal of Contemporary Pediatrics, 2024)
Systemic lupus erythematosus is an autoimmune inflammatory disease with complex etiology. Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) represent a spectrum of skin lesions characterized by rashes, exfoliation, and sloughing usually following drug intake. Occasionally, TEN-like cutaneous manifestations have also been described with systemic lupus erythematosus. Recognition of lupus in a child presenting with TEN-like skin changes is clinically challenging and requires a high degree of suspicion. We present a case of a 9-year-old female with SJS/TEN like lesions following drug intake and on evaluation was found to have systemic lupus erythematosus.